Analysis of Work Fatigue Based on Dhikr Behaviour among Administration Workers in Higher Education - Aisy Rahmania; Eka Rosanti; Imroatul Istiqomah (Universitas Nahdlatul Ulama Surabaya, 2024)
Administrative workers have the potential to experience work fatigue. Fatigue conditions among workers can affect work productivity and can even cause health problems. Work fatigue can be characterized by decreased reaction time. The longer the reaction time indicates that a worker is getting higher fatigue level. Dhikr is a religious activity that can create peace of mind and encourage the muscles in the body to relax. A relaxed body condition will help workers not experience excessive fatigue. This research is a descriptive analytical study with a cross-sectional approach. The sample was taken using simple random sampling as many as 70 administrative workers in higher educational institution. The aim of this research is to analyze the effect of the dhikr behaviour intensity on the level of work fatigue. The results of the research show that the intensity of the dhikr behaviour does not affect the level of work fatigue among administrative workers in higher education.